Association of 25-hydroxyvitamin D and Anemia parameters in elderly with anemia of inflammation and non-inflammation (Bangladesh Journal of Medical Science, 2018)
Background: Vitamin D deficiency and anemia are conditions commonly in eldery. Both result in significant morbidity in eldery. Relationship between 25-hydroxyvitamin D and anemia need to be concern, particularly in the elderly. including those characterized by inflammatory processes. The aim of this study is to analyze association and differentiations between of 25-hydroxyvitamin D levels and anemia parameters in elderly with anemia inflammation and non-inflammation.Methods: An observational study, at Posyandu Lansia Puskesmas Sokaraja, was conducted among 40 subjects aged ≥60 years consecutively, between September - November 2015. 25-Hydroxyvitamin D, hemoglobin levels, hematocrit and red blood cell counts were measured. 25-Hydroxyvitamin D deficiency defined in level